Enhancing Student Learning Outcomes Through Visual Teaching Materials in Christian Religious Education for Elementary Schools - Fasuba, Ayodeji Francis (EDUCARE: Journal of Primary Education, 2024)
This study investigated the impact of visual instructional materials on the learning outcomes of primary school pupils in Christian Religious Studies (CRS) in Ado-Ekiti, Ekiti State, Nigeria. It utilized relevant pictures depicting Bible stories during the instructional process. A quasi-experimental design was employed, featuring one experimental group and one control group. The participants consisted of 119 primary 5 pupils offering CRS, selected from the central area of Ado-Ekiti through a simple random technique. Data were collected using the Christian Religious Studies Achievement Test (CRSAT), and the research hypotheses were analyzed using t-tests and Analysis of Variance (ANOVA). The findings revealed a significant difference in the post-test scores between the experimental and control groups, indicating the effectiveness of the chalk and talk method supplemented with visual instructional materials. However, the interaction between treatment and gender was found to be statistically insignificant. Based on these findings, it is recommended that primary school teachers in Christian Religious Studies (CRS) adopt this method during the instructional process. The study was conducted within a constrained timeframe due to the school calendar. This study's contribution provides empirical validation of the effectiveness of the "chalk and talk" method supplemented with visual teaching materials in improving students' learning performance in Christian Religious Studies (CRS) subjects at the elementary school level. The findings provide important insights for developing effective teaching strategies in the elementary education curriculum. In addition, this study acknowledges the time constraints due to school schedules and recommends further research conducted over a more extended period or in different contexts to gain a broader understanding.